The Arabidopsis PHB3 is a pleiotropic regulator for plant development. (2nd November 2019) - Huang, Ruihua; Yang, Chengwei; Zhang, Shengchun
ABSTRACT: Prohibitins (PHBs) are composed of an obviously conserved protein family in eukaryotic cells. Despite the extensive and in-depth research of mammalian PHB1 and PHB2, the plant prohibitins functions are not completely elucidated and little is known about their mechanism of action. This review focuses on the current knowledge about the protein subcellular localization, interaction proteins and target genes of PHB3. Furthermore, we discussed the roles of PHB3 protein in plant growth and development, plant responses to abiotic or biotic stresses and its participation in phytohormonal signaling.